Gunung Padang Megalithic Site Management Strategy: SWOT Analysis Approach for Sustainable Tourism Development - Wahyu Handayani, Tri; Viantara, Risma; Rismayadi, Hilman (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2024)
This study focuses on the development and preservation of the Megalithic Site of Gunung Padang in Cianjur, West Java, which is one of the largest megalithic sites in Southeast Asia. The purpose of this research is to identify the potential and challenges in managing this site as a sustainable cultural tourism destination. The research methods used include a SWOT (Strength, Weakness, Opportunity, Threat) analysis to evaluate aspects of topography, accessibility, and environmental sustainability. The findings show that proper management and the development of educational tourism facilities are crucial to maintaining the site's preservation and enhancing visitor experiences. The study also recommends improving accessibility and implementing sustainable waste management as part of conservation efforts. Thus, this research provides significant contributions to the preservation of cultural heritage and the development of sustainable tourism in West Java.